2021
DOI: 10.1002/jmv.26917
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of itraconazole against SARS‐CoV‐2

Abstract: Although vaccination campaigns are currently being rolled out to prevent coronavirus disease (COVID‐19), antivirals will remain an important adjunct to vaccination. Antivirals against coronaviruses do not exist, hence global drug repurposing efforts have been carried out to identify agents that may provide clinical benefit to patients with COVID‐19. Itraconazole, an antifungal agent, has been reported to have activity against animal coronaviruses. Using cell‐based phenotypic assays, the in vitro antiviral acti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 36 publications
3
32
0
Order By: Relevance
“…In this context, the pharmacological redistribution of cholesterol and impaired lipid raft formation hampers the SARS-CoV-2 SARS-CoV-2 entry, and consequently the virus replication (34,(43)(44)(45). In line with the results obtained here with simvastatin pretreatment, other drugs that affect not only the synthesis but also the traffic of cholesterol through the endosomal pathway, such as itraconazole, fluoxetine and amitriptyline showed promising results as adjuvant therapy for COVID-19 (42,46,47).…”
Section: Discussionsupporting
confidence: 78%
“…In this context, the pharmacological redistribution of cholesterol and impaired lipid raft formation hampers the SARS-CoV-2 SARS-CoV-2 entry, and consequently the virus replication (34,(43)(44)(45). In line with the results obtained here with simvastatin pretreatment, other drugs that affect not only the synthesis but also the traffic of cholesterol through the endosomal pathway, such as itraconazole, fluoxetine and amitriptyline showed promising results as adjuvant therapy for COVID-19 (42,46,47).…”
Section: Discussionsupporting
confidence: 78%
“…The findings of this study were comparable with other large screening studies that identified potential anti-SARS-CoV-2 agents and compounds, although in vivo efficacy, toxicity, and pharmacokinetic investigation of the selected hits in this report did not support novel application against SARS-CoV-2. 9,12,25,27,29,[46][47][48][49][50] Together, these studies demonstrate that drug repurposing technology can identify potential agents for rapidly spreading novel pathogens, as in the case of remdesivir, which has been used to treat patients with severe COVID-19. Although preclinical drug repurposing studies may provide a means of identifying potential agents and avoiding some of the limitations of traditional clinical development, the findings of this study suggest that results from in silico or in vitro studies should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 89%
“…Aspergillosis, candidiasis, and cryptococcosis [22]. SARS-CoV-2 [23,24], influenza virus [25], Ebola virus [26][27][28], Parechovirus A3 [29],…”
Section: Echinocandinsmentioning
confidence: 99%
“…Interestingly, NPC1 also emerged as a candidate drug target for other enveloped viruses, namely IAV and SARS-CoV-2. Viral replication rates were decreased in cells in which NPC1 was functionally blocked, and the increased endolysosomal cholesterol levels were suggested to interfere with the proper insertion of the fusogenic IAV hemagglutinin domains and the SARS-CoV-2 spike protein, thus affecting virus uncoating [23][24][25].…”
Section: Itraconazole Directly Interacts With the Endolysosomal Chole...mentioning
confidence: 99%